1975
DOI: 10.1080/00288330.1975.9515572
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and tidal variations in the hydrology of Wellington harbour

Abstract: Observations were made on several hydrological features of Wellington Harbour, New Zealand (41° 16' S, 174° 51' E) during 1970 to 1972. These suggest that the harbour is topographically partially isolated from oceanic influences, and that waters within the harbour undergo efficient mixing.Monthly mean sea-surface temperatures ranged seasonally between 10.5°c and 18.5°c, and some stratification was observed during summer and winter. Salinities usually ranged from 33.5% O to 34.5% O , and water transparency by S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0

Year Published

1979
1979
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 6 publications
3
51
0
Order By: Relevance
“…Several authors have suggested that Wellington Harbour is at least partially isolated from the shelf area immediately outside the harbour entrance (Maxwell 1956, Booth 1975, Harris 1990). The Harbour is a sheltered, well-mixed, nutrient-rich, semi-enclosed body of water (85 km2 in area) with a flushng time of -9 d (Maxwell 1956, Brodie 1958, Booth 1975, Heath 1977. By comparison, the south coast shelf system (Cook Strait) is a high-energy, very exposed coastline.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have suggested that Wellington Harbour is at least partially isolated from the shelf area immediately outside the harbour entrance (Maxwell 1956, Booth 1975, Harris 1990). The Harbour is a sheltered, well-mixed, nutrient-rich, semi-enclosed body of water (85 km2 in area) with a flushng time of -9 d (Maxwell 1956, Brodie 1958, Booth 1975, Heath 1977. By comparison, the south coast shelf system (Cook Strait) is a high-energy, very exposed coastline.…”
Section: Discussionmentioning
confidence: 99%
“…Details of the plankton sampling programme, including the areas, times, and methods have been described by Booth (1974Booth ( , 1975Booth ( , 1977. In brief, three plankton stations were occupied in the Bay of Islands (35°1 5'S, 174°10'E) (Apr 1970-Dec 1971, four in Wellington Harbour (41°16'S, 174°51'E) (May 1970-Feb 1972 and four at Raumati Beach (40°56'S, 174°5…”
Section: Sampling Areas and Methodsmentioning
confidence: 99%
“…8'E) (Jun 1971-Jun 1972; the positions of these stations are given in Booth (1977;figs 1 & 2). Details of the hydrology of the Bay of Islands and Wellington Harbour during the sampling period are given in Booth (1974Booth ( , 1975.…”
Section: Sampling Areas and Methodsmentioning
confidence: 99%
See 2 more Smart Citations